2020
DOI: 10.1111/jfr3.12590
|View full text |Cite
|
Sign up to set email alerts
|

Analysing flash flood risk perception through a geostatistical approach in the village of Navaluenga, Central Spain

Abstract: Flash floods are unexpected events, which evolve rapidly and affect relatively small areas. The short time available for minimising risks requires preparedness and active response. In this context of risk management, the flood risk perception of the local population is the first step towards achieving resilience of people and communities. Although flood risk perception has intrinsic spatial variability, few previous studies take this into account. This paper explores the spatial variability of flash flood risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Despite its importance, only three (3.2 %) of the reviewed papers performed uncertainty analysis. Nazeer and Bork (2019) observed variations in the final results that changed input variables, and Feizizadeh and Kienberger (2017) and Guo et al (2014) applied a Monte Carlo simulation and set pair analysis, respectively.…”
Section: Uncertainty Sensitivity and Validationmentioning
confidence: 99%
“…Despite its importance, only three (3.2 %) of the reviewed papers performed uncertainty analysis. Nazeer and Bork (2019) observed variations in the final results that changed input variables, and Feizizadeh and Kienberger (2017) and Guo et al (2014) applied a Monte Carlo simulation and set pair analysis, respectively.…”
Section: Uncertainty Sensitivity and Validationmentioning
confidence: 99%
“…In this way, the approach can support decision-making. We thus offer these results as a springboard to support policy-makers, local authorities and civil protection in planning medium- and long-term actions to reduce hydrological disasters [ 105 106 ]. As rainfall erosivity is projected to increase by at least 35% globally by 2070 [ 107 ], the probability of hydrological hazards will also show similar trends.…”
Section: Discussionmentioning
confidence: 99%
“…In today's context, it is observed that most of the MFIs in Sri Lanka adapt short term strategies to generate a high return and then exit from the business. Saturation of existing operational areas before large-scale horizontal expansion may be a better growth strategy, reducing cost and increasing efficiency in caseload and overall management (Guardiola-Albert et al, 2020). Hence, the first step is to create a stated objective and motivation from the owners and management to manage risk on a daily basis before it arises and/or as it becomes recognized.…”
Section: Literature Reviewmentioning
confidence: 99%